2020
DOI: 10.3389/fonc.2020.00341
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Based on Systemic Immune-Inflammation Index to Predict Survival of Tongue Cancer Patients Who Underwent Cervical Dissection

Abstract: Aim: The aim of this study was to evaluate the prognostic significance of the preoperative systemic immune-inflammation index (SII) and to establish a nomogram for prediction of survival of tongue squamous cell carcinoma (TSCC) patients who underwent primary surgery and cervical dissection.Methods: 120 patients diagnosed with TSCC who underwent primary tumor and neck dissection without preoperative treatment were included to develop the nomogram. This model was externally validated in an independent data cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 41 publications
5
62
0
3
Order By: Relevance
“…This discrepancy may be due to the socioeconomic differences between black people and other races in specific areas (Weng & Korte, 2012). The results showed that higher pathological stage (grade) and M1 stage were independent risk factors for BMC patients, which is consistent with the results of scholars in OSCC and TSCC research (Li et al., 2017; Lu et al., 2020; Wang et al., 2018). However, the two factors were eliminated in the process of using BIC to optimize the model and avoid over‐fitting.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This discrepancy may be due to the socioeconomic differences between black people and other races in specific areas (Weng & Korte, 2012). The results showed that higher pathological stage (grade) and M1 stage were independent risk factors for BMC patients, which is consistent with the results of scholars in OSCC and TSCC research (Li et al., 2017; Lu et al., 2020; Wang et al., 2018). However, the two factors were eliminated in the process of using BIC to optimize the model and avoid over‐fitting.…”
Section: Discussionsupporting
confidence: 88%
“…A nomogram is a convenient and advanced method for estimating clinical events using multiple known variables and is widely applied in the prognostic prediction of most cancer types (Balachandran, Gonen, Smith, & DeMatteo, 2015; Iasonos, Schrag, Raj, & Panageas, 2008; Lu et al., 2020). But, most nomograms are based on the traditional Kaplan–Meier approach and Cox proportional hazard model, ignoring the occurrence of competitive events, thereby misjudged the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SII was a convenient, low-cost, and effective inflammatory indicator to predict the prognosis of tumors. Previous studies have only reported the use of SII in nomograms for gastric and tongue cancer ( 22 , 23 ). Here, we report for the first time that nomograms based on SII can effectively predict postoperative HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a nomogram, a novel statistical prediction model, can accurately estimate individual survival and guide plans for follow-up by integrating multiple factors (14). Furthermore, several studies have indicated the favorable results of nomogram (15) and its utility in various cancers (16)(17)(18)(19). To date, an effective nomogram for PLN-PaCs has never been developed.…”
Section: Introductionmentioning
confidence: 99%